2023
DOI: 10.32479/ijeep.13765
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Production on the Introduction of ICT and the Growth of AIC in Kazakhstan

Abstract: The presented work is devoted to the organization of the electric power industry and the agro-industrial complex of Kazakhstan. Here is given an economic analysis of the production capacity of the development of power plants. It is noted that more than 80% of electricity generation is carried out by coal-fired thermal power plants. Important attention is paid to the significant wear and tear of machinery and equipment at thermal power plants and state district power plants. The key focus of the work is on econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Furthermore, the ARDL method revealed that oil and natural gas production affects people's health expenditures in the short term, but not in the long term. Smagulova et al (2023) used econometric modeling to determine the impact of electricity generation and digital farms on agricultural production in Kazakhstan and to identify patterns. They found that the digitalization of the energy and agro-industrial sectors contributes to economic growth and recommended encouraging the construction of new environment-friendly energy facilities and adopting measures to increase alternative energy investments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ARDL method revealed that oil and natural gas production affects people's health expenditures in the short term, but not in the long term. Smagulova et al (2023) used econometric modeling to determine the impact of electricity generation and digital farms on agricultural production in Kazakhstan and to identify patterns. They found that the digitalization of the energy and agro-industrial sectors contributes to economic growth and recommended encouraging the construction of new environment-friendly energy facilities and adopting measures to increase alternative energy investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first quarter of 2020, the production was 1470 million kWh, whereas in the first quarter of 2021, it increased to 2005.5 million kWh. In addition to fossil fuels and renewable energy sources, Kazakhstan also has a significant nuclear energy production potential due to its uranium mines (Smagulova et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a favorable correlation between economic growth and overall energy demand (Wang et al, 2018;Muhammad, 2019;Mohsin et al, 2021). The more general correlation between economic growth and the development of renewable energy has gotten less attention, and to yet, no empirical study on this relationship has been done in the set of Turkey and Kazakhstan (Smagulova et al, 2015;Moldabekova et al, 2022). This study aims to explore the relationship between the use of renewable energy and economic development in the case study countries using a novel technique compared to another research.…”
Section: Introductionmentioning
confidence: 99%
“…Smart grids have the potential to make significant contributions to environmental sustainability by mitigating the inherent uncertainty of renewable energy sources (RESs) which can be unstable and require a more complex grid. SGs maximize the potential of RESs by enabling their seamless integration into the existing grid infrastructure and lessening the reliance on fossil fuels, thus helping to combat climate change and reduce greenhouse gas emissions [10,[29][30][31]. Smart grids enhance the efficient utilization of energy resources, thereby minimizing waste and encouraging energy conservation [32].…”
Section: Introductionmentioning
confidence: 99%